Admission competition for medical residency in Peru: Characteristics, preferences, and proposals from physicians who are preparing for taking the national medical residency examination in 2011 - Galán-Rodas, Edén (2010)
Objetive: To describe features, preferences, and proposals from physicians that are preparing themselves to take the 2011 National Medical Residency Examination in Peru.   Material and ethods: This is a descriptive study, considering a referential population including 4328 candidates, according to the 2010 National Medical Residency Examination. The Epidat 3.1 statistical software was used, with a 95% confidence limit, and a 5% precision value, and the simple size was established in 353 physicians. A self-applicable and previously validated questionnaire was previously used as a pilot in 20 candidates.   Results: Of the 416 surveyed physicians (median age, 27 years), most of them come from provinces outside Lime (52.6%). Nearly half of all physicians (42.5%) are currently working, 79.5 of them in the private sector and 79.2 on an outsourcing basis. Nearly half of all candidates (48.6%) performed their rural healthcare service (SERUMS, according to its Spanish initials) in extremely poor areas in Peru (Quintile I). More than half of the candidates (54.3%) had already taken the Medical Residency Examination in the past. Nearly half of the candidates (48,6%) do not agree with the current status for the National Medical Residency Examination, 67.5% prefer a single national examination, and 39,2% prefer that the contest is separated for each specialty. More than one third (38.9%) considered that the examination should be led by CONAREME (National Commission for Medical Residency) and each Medical School. More than half of the candidates do not agree with the increase of the so-called captive places, and 78.1% disagreed with the proposal by the Ministry of Health to establish an additional mandatory period of work for medical specialists in the less developed areas in the country.   Conclusions: The majority of candidate physicians surveyed come from medical schools outside Lima, they do not have a family of their own to care for, les tan half of them are properly employed, and most of those who have a job are in an outsourcing schedule. Most of all candidates do not agree with the current process for the National Medical Residency Examination and they favor a single examination according to medical specialties, and female physicians prefer clinical areas for specialization. Most of the candidates do not agree with the proposal to have an additional mandatory period of time working in the most depressed areas, and they propose that the process for the National Medical Residency Examination must be more transparent, and that the charge by CONAREME as a requisite for taking the examination must be eliminated.